Evidence-Based Theory of Market Manipulation And Application: The Malaysian Case - Heong, Yin Yun (2010)
According to Part IX Division 1 in Securities Industry Act 1983 of Malaysia Law, stock market manipulation is defined as unlawful action taken either direct or indirectly by any person, to affect the price of securities of the corporation on a stock market in Malaysia for the purpose which may include the purpose of inducing other persons. Extending the framework of Allen and Gale (1992), the Author presents a theory based on the empirical evidence from prosecuted stock market manipulation cases in Malaysia. The first part of this paper reviews the market manipulation trading strategies which are used in the selected prosecuted corporate crimes, and three main manipulation schemes are coined, namely the volume-based, accounting-based and information-based manipulation. These three schemes are commonly used by the syndicates or insiders to defraud investors who making their investment decisions based technical, fundamental and sentimental analysis. This theory is thus can be adopted as an analytical tool for understanding, explaining and making predictions on the given subject matter. The second part of this paper surveys the PN17 companies in Bursa Malaysia, through hypothetical testing grounded on the analytical theory. PN17 companies are the listed companies with huge deficit shareholders fund, and represent the worst shareholders wealth destruction amongst all listed companies in Malaysia. While bad management or deteriorating industry fundamental or faltering competitive position of the company is usually the key reasons for the poor performance, the central question is ―are these PN17 companies manipulated?‖ The result reveals persuasively towards a positive correlation between potential manipulation and most of the PN17 companies.In other words, it is believed that the failure of most of these PN17 companies could have been engineered in contravention of regulations as the Securities Commission prescribed. While the regulatory environment in Malaysia is equitably mature, the paper concludes by providing suggestions on how certain reform could be performed to strengthen the execution and the enforcement of the regulators.